The systematics and phylogenetics of the Sycoecinae (Agaonidae, Chalcidoidea, Hymenoptera) - Noort, Simon van (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1993)
The Sycoecinae are a distinct and well-defined subfamily of old world fig wasps (Agaonidae, Chalcidoidea 1 Hymenoptera) , exclusively associated with the figs of Ficus species (Moraceae). The most likely sister group of the Sycoecinae was determined to be the Sycoryctini (Sycoryctinae) based largely on synapomorphies of the underside of the head. 67 sycoecine species and 3 subspecies were recognised and included in a phylogenetic analysis of the subfamily. This analysis clearly delimited six genera (four African and two extra-African), although the phylogenetic relationships between the genera were not strongly supported and remain flexible. Comparisons of the phylogeny of the Sycoecinae with the classifications of the Agaoninae and their host fig trees (Ficus, Moraceae) suggest a degree of cospeciation sensu lato. Numerous homoplasies were detected within the Sycoecinae, some of which were shared with another group of fig wasps that also enter the fig to oviposit, the Agaoninae. The anatomy of the figs apparently provides strong selection pressures that have resulted in both parallelisms and convergences within and between the two subfamilies. Among the 67 species and 3 subspecies that were recognised, 43 species and 2 subspecies are described as new. The males of three previously recognised species are also described for the first time. One generic and two specific synonyms are established together with five new combinations. Keys are provided to the genera and species, for both sexes.
Keywords: Agaonidae; Chalcid wasps; Fig wasp -- South Africa